WOMEN’S LANGUAGE IN KIM KARDASHIAN’S INTERVIEW WITH VOGUE - Oktaviari Widiastuti (PARADIGM: Journal of Language and Literary Studies, 2022)
As a subordinate group in society, women should speak and behave politely. This situation makes women have their characteristics when they speak. Kim Kardashian is a celebrity who has influenced many people through her fashion sense and career advancement as a celebrity and businesswoman. This research aims to examine the women's language characteristics that occurred in Kim Kardashian's utterances in her interview with Vogue. The instrument of this research is a document. First, the data were collected from Kim Kardashian’s interview with Vogue. The data were selected and identified the women's language characteristics that appeared in Kim Kardashian's utterances. Then the research showed the research findings by presenting the data and analysis. There are 360 data classified as women's language characteristics, which consist of 106 intensifiers, 84 hedges, 71 rising intonation, 34 emphatic stress, 31 hypercorrect grammar, 20 empty adjectives, five tag questions, 4 super polite forms, 3 specific colours, and 2 avoidances of swear words. An intensifier is a characteristic that Kim Kardashian frequently uses because she wants to express her certainty about her utterances and make them firmer, so the addressee will take her statements seriously and get the point of her statement.